6X+27+7X-9=96

Simple and best practice solution for 6X+27+7X-9=96 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6X+27+7X-9=96 equation:


Simplifying
6X + 27 + 7X + -9 = 96

Reorder the terms:
27 + -9 + 6X + 7X = 96

Combine like terms: 27 + -9 = 18
18 + 6X + 7X = 96

Combine like terms: 6X + 7X = 13X
18 + 13X = 96

Solving
18 + 13X = 96

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-18' to each side of the equation.
18 + -18 + 13X = 96 + -18

Combine like terms: 18 + -18 = 0
0 + 13X = 96 + -18
13X = 96 + -18

Combine like terms: 96 + -18 = 78
13X = 78

Divide each side by '13'.
X = 6

Simplifying
X = 6

See similar equations:

| 2(8y-4.4)+7=6(7y-0.3) | | (y+7)/(y^2-8y+7)=(1/(y-1))-(1/(y-7)) | | (x^2-16)/(x^2-3x-4)=0 | | (0.25+0.083+0.3)x0.3/0.5 | | 11(x-2)-4=9x+4 | | -75x^2+290x=240 | | 4X+20+6X+0=90 | | 5(y+2.6)=12y-19.2 | | 4X+20+6X+O=90 | | 3X+144+2X+1=180 | | 3/(7x+4)=7/(x-2) | | 10+3x=2x+12 | | b^2+5b+b=0 | | y=-12x^2+48x-23 | | 5(x+2)=2x+28 | | 63x^2-7=0 | | 11.6y+3=3.8y+38.10 | | (-5x+1)(25x^2+5x+1)=0 | | 6X+49+2X+11=180 | | 7y-1=4+9y | | 9-3=x | | 8X-105+9X-38=180 | | x^2+5x+2x+10= | | (5x+1)(5x+1)(5x+1)=0 | | 7X-75+4X+90=180 | | 8X-41+6X+75=146 | | 4(x-3)=3-6(x-7) | | 8X-41+6X+75=14 | | -3x-3=6-6x | | (6/(x^2-2x-8))+(6/(x+2))=(1/(x-4)) | | 18x+4(4x-3)=4(6x+4)-4 | | -2j+(3j+1)-3(6+j)=-1 |

Equations solver categories